ORGANIZE ADDITIONAL CLEANING BY IMPROVING THE DESIGN OF THE PNEUMATIC CONVEYING DEVICE - Abdukarimov Tolibkhon Tokhirkhon oglu; Shamshidinov Ibragimkhon Muminkhon oglu (Galaxy International Interdisciplinary Research Journal, 2022)
This article puts forward scientific and technical ideas for organizing additional cleaning by improving the design of the pneumotransport device.